Membangun Karakter dan Integritas Bagi Narapidana Perempuan di Rutan Tanjung Gusta, Medan - Tan, Kim Hek; Gani, Petrus; Sudarso, Andriasan; Mipo, Mipo; Yanris, Gomal Juni (Lembaga Dongan Dosen, 2024)
Inmates are individuals who have made mistakes, requiring them to serve a sentence that entails the loss of freedom in the outside world and a life within a correctional facility. Consequently, inmates live isolated from society, family, and within limited surroundings. Feelings of guilt and shame arise due to their unlawful actions, and they must confront prison life with strict rules and high discipline, which becomes an additional burden for them and impacts their psychological well-being. Through the implementation of this PkM, it is hoped that inmates can build self-confidence, accept themselves, develop honesty, a strong work ethic, strive for self-improvement, and demonstrate integrity by exhibiting good behavior in life. Thus, when they eventually reintegrate into society, their environment will be more accepting of them. The purpose of the outreach program at Tanjung Gusta Detention Center is to help inmates become well-rounded individuals, devout, and responsible for themselves, their families, and society. The program's method involves direct, face-to-face counseling sessions that present material to female inmates. Through the counseling provided by lecturers from STIE Eka Prasetya, IBBI University, Labuhanbatu, and in collaboration with a pastor from the Parousia Christian Church, it is hoped that the character and morals of the inmates will be positively shaped developing honesty, responsibility, dignity, and integrity. The results of this community service show the enthusiasm and positive interaction of the inmates to increase their knowledge and awareness, as evidenced by their willingness to participate in the activities, allowing the program to proceed smoothly.